Evaluation of Analgesic and Anti-Inflammatory Activity of Ibuprofen-Pregabalin in Animal Models - Chidambarann Suthakaran; Gopalakrishnan Senthil (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Despite an enhanced recognition of the molecular mechanisms of nociception, existing analgesic drugs continue to remain restricted in terms of efficacy. Since all single analgesic drugs are not effective in all patients at all times, there is a need either to develop new and more effective drugs or to identify favourable combinations of drugs that are already available. Aim: To evaluate the analgesic and anti-inflammatory activity of combined use of ibuprofen and pregabalin in animal models of pain and inflammation. Materials and Methods: The animals (Swiss albino mice and Wistar rats) were randomly divided into eight groups with six animals in each group. Analgesia was assessed by acetic acid induced writhing and tail immersion methods in mice and hot plate method in rats. Paw oedema model in rats after induction with 0.1 mL of 1% carrageenan was used to assess the anti-inflammatory activity. The percentage inhibition of writhes and prolongation of reaction time were used for assessing analgesic activity and reduction in paw volume was used for assessing anti-inflammatory activity. The results obtained were analysed by ANOVA followed by Tukey HSD Post-hoc Test. Results: There was a significant diminution in the amount of writhing in all the groups tested when compared to the control group and the highest percentage inhibition of pain was seen with high dose combination group. There was a statistically significant increase in reaction time at all time points compared to baseline values in all treatment groups in the hot plate and tail immersion methods. A notable observation was that the degree of inhibition of paw oedema was greater in the combination groups than ibuprofen alone or the standard anti-inflammatory drug diclofenac while pregabalin alone exhibited negligible anti-inflammatory activity. Conclusion: The present study displayed prominent analgesic effect and serves as a proof-of-principle study for considering the combination of ibuprofen and pregabalin as a lead for the development of new dual-action analgesic drugs. If confirmed, in additional models of acute and/or chronic pain this combination might be useful in the clinical management of pain associated with inflammation.